Creating Ourselves : African Americans and Hispanic Americans on Popular Culture and Religious Expression - Valentin, Benjamin; Pinn, Anthony B. (Book collections on Project MUSE., 2009)
Analyzes the religious and theological significance of African-American and Hispanic-American popular culture, structured in part as a dialogue between scholars from both ethnic groups.